2018
DOI: 10.1021/acs.est.8b03730
|View full text |Cite
|
Sign up to set email alerts
|

Tris(1,3-dichloro-2-propyl) Phosphate Exposure During the Early-Blastula Stage Alters the Normal Trajectory of Zebrafish Embryogenesis

Abstract: Tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) is an organophosphate flame retardant used around the world. Within zebrafish, we previously showed that initiation of TDCIPP exposure during cleavage (0.75 h post-fertilization, hpf) results in epiboly disruption at 6 hpf, leading to dorsalized embryos by 24 hpf, a phenotype that mimics the effects of dorsomorphin (DMP), a bone morphogenetic protein (BMP) antagonist that dorsalizes embryos in the absence of epiboly defects. The objective of this study was to (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Phenotyping for DV defects has been previously used for the detection of early developmental toxicity in large-scale screens for drugs or small molecules that target developmental signaling pathways. Specifically, because BMP signaling primarily regulates DV patterning, studies from our lab and other groups have used dorsalization and ventralization phenotypes as indicators of BMP signaling defects caused by BMP inhibitors such as DMP, activators such as 4 -H (Dasgupta et al, 2018;Vrijens et al, 2013;Yu et al, 2008), or knockdown of BMP pathway-specific genes such as szl and chd (Dasgupta et al, 2017). However, our work also showed that DV defects are not necessarily readouts of direct impacts on BMP signaling because two structurally diverse chemicals, namely tris(1,3-dichloro-2propyl)phosphate (TDCIPP, an environmental chemical) and ciglitazone (a drug), induced dorsalization and ventralization phenotypes, respectively, without corresponding impacts on BMP signaling based on mRNA sequencing and pSMAD 1/5/9 staining (Cheng et al, 2019;Dasgupta et al, 2018;Dasgupta et al, 2017).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Phenotyping for DV defects has been previously used for the detection of early developmental toxicity in large-scale screens for drugs or small molecules that target developmental signaling pathways. Specifically, because BMP signaling primarily regulates DV patterning, studies from our lab and other groups have used dorsalization and ventralization phenotypes as indicators of BMP signaling defects caused by BMP inhibitors such as DMP, activators such as 4 -H (Dasgupta et al, 2018;Vrijens et al, 2013;Yu et al, 2008), or knockdown of BMP pathway-specific genes such as szl and chd (Dasgupta et al, 2017). However, our work also showed that DV defects are not necessarily readouts of direct impacts on BMP signaling because two structurally diverse chemicals, namely tris(1,3-dichloro-2propyl)phosphate (TDCIPP, an environmental chemical) and ciglitazone (a drug), induced dorsalization and ventralization phenotypes, respectively, without corresponding impacts on BMP signaling based on mRNA sequencing and pSMAD 1/5/9 staining (Cheng et al, 2019;Dasgupta et al, 2018;Dasgupta et al, 2017).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…This was further supported by our mRNA-seq data, as neither bmp2 nor psmad1/5/9 transcripts were significantly altered after exposure to 12.5 μM ciglitazone, 0.078 μM DMP, or 12.5 μM ciglitazone + 0.078 μM DMP. Similarly, exposure to tris(1,3-dichloro-2-propyl) phosphate (TDCIPP)—a high-production volume organohalogen flame retardant—induced dorsoventral patterning defects in the absence of effects on BMP signaling within developing zebrafish embryos (Dasgupta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum tolerated concentrations for DMP and ciglitazone co-exposures were optimized based on preliminary experiments that tested combinations of 0.078 or 1.56 μM DMP in the presence or absence of 9.375, 12.5, or 15 μM ciglitazone. Although 0.625 µM DMP was used in our prior studies (Dasgupta et al, 2017; Dasgupta et al, 2018), we relied on 0.078 µM DMP since co-exposure with 0.625 μM DMP and 12.5 μM ciglitazone resulted in a significant increase in mortality. At 8 hpf, embryos were fixed overnight in 4% PFA/1× PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…to be transferred to offspring, resulting in developmental neurotoxicity (Du et al, 2015;Liu et al, 2013;Yu et al, 2017;Zhang et al, 2018a;Zhang et al, 2018b). Additional adverse effects of OPE exposure include developmental toxicity (Dasgupta et al, 2018;Dasgupta et al, 2017;Jacobsen et al, 2017;Li et al, 2018;Oliveri et al, 2018;Yan & Hales, 2018), oxidative stress (Chen et al, 2015a;Chen et al, 2015b;Gu et al, 2019;Yan et al, 2017), thyroid disruption (Fernie et al, 2017;Hill et al, 2018;Liu et al, 2019;Preston et al, 2017), neurotoxicity (Andresen et al, 2004;Hong et al, 2018;Shi et al, 2018;Slotkin et al, 2017), carcinogenicity (Hoffman et al, 2017b;Ni et al, 2007;Van den Eede et al, 2013b), endocrine disruption (Arukwe et al, 2016;Kojima et al, 2013;Kojima et al, 2016;, and cellular toxicity (Shen et al, 2019;Canbaz et al, 2017;Crump et al, 2012;Shen et al, 2019;Su et al, 2014a agonists, similar to their parent compound TBOEP as well as TEHP, and TNBP (Kojima et al, 2016). Metabolism can significantly influence the accumulation and adverse effects of chemicals in organisms, however the transformation of OPEs and distribution of their metabolites are still unknown.…”
Section: Metabolismmentioning
confidence: 99%